Antioxidant and Anticancer Efficacies of Anethum graveolens against Human Breast Carcinoma Cells through Oxidative Stress and Caspase Dependency. (4th May 2021) - Al-Oqail, Mai M.; Farshori, Nida N.
Abstract : Anethum graveolens, belonging to the family Apiaceae, has been extensively used for medicinal and therapeutic purposes since long. Plants encompass rich number of effective constituents with less toxicity. Thus, nowadays, the attempts are being made to search plant constituents that can prevent and reverse the chronic diseases, such as cancer. In this study, an in vitro antioxidant and anticancer efficacies of Anethum graveolens (AG-ME) were studied on human breast (MCF-7), lung (A-549), and cervical (HeLa) carcinoma cell lines. The antioxidant efficacies of AG-ME were evaluated by total antioxidant, DPPH radical scavenging, H2 O2 scavenging, and ferrous reducing antioxidant assays. Further, the anticancer potential of AG-ME was also determined against different cancer cell lines. The AG-ME exhibited strong antioxidant activities as observed by antioxidant assays. AG-ME also showed a dose-dependent anticancer/cytotoxic potential against MCF-7, A-549, and HeLa cell lines. The AG-ME-induced reduction in GSH and increase in SOD activities indicates the role of oxidative stress in AG-ME-induced MCF-7 cell death. The results also exhibited that AG-ME triggered ROS production and significantly reduced MMP level. Moreover, a dose-dependent increase in caspase-3 and caspase-9 activities suggests that the AG-ME-induced MCF-7 cell death is caspase-dependent. Together, the present study provides reasoning and reassurance for the uses of A. graveleons for medical purposes as an antioxidant and anticancer agent. Additional investigations are required to examine biological and anticancer activities under an in vivo system to discover a possible beneficial use of AG-ME against diseases.